Pengaruh Literasi Keuangan Syariah Terhadap Keputusan Penggunaan Inklusi Keuangan Digital Pada Generasi Millenial di Kota Makassar - Amriani Amriani; Baso Amang; Masdar Mas’ud (Departement of Mathematics Education, 2023)
This research was conducted with the aims of: (1) analyzing basic knowledge of Islamic financial literacy influencing digital financial inclusion in the millennial generation; (2) analyzing Islamic contracts influencing digital financial inclusion in the millennial generation; (3) analyze Islamic savings and loans that affect digital financial inclusion in the millennial generation; (4) analyzing sharia insurance has an effect on digital financial inclusion in the millennial generation; (5) analyzing Islamic investment has an effect on digital financial inclusion in the millennial generation. This type of research is quantitative research by distributing questions in the form of questionnaires to respondents, namely the millennial generation in Makassar City, the type of data used is primary data with a sample size of 100 respondents. The analytical tools used in this study are validity test, reliability test, classical assumption test: normality test, linearity test, multicollinearity test, autocorrelation test, hypothesis test: multiple linear regression model test, t test using the SPSS program. The results of this study indicate that: (1) basic knowledge of Islamic financial literacy has a positive and not significant effect on digital financial inclusion in the millennial generation; (2) Islamic contracts have a positive and significant effect on digital financial inclusion in the millennial generation; (3) Islamic savings and loans have a negative and insignificant effect on digital financial inclusion in the millennial generation; (4) sharia insurance has a positive and insignificant effect on digital financial inclusion in the millennial generation; (5) sharia investment has a negative and insignificant effect on digital financial inclusion in the millennial generation. The millennial generation in the city of Makassar is expected to be able to apply the knowledge of Islamic finance that they already have to better manage their personal finances and be able to run the financial system in accordance with sharia principles.